Anomalous position of Paleozoic faults of Western Donbas - Goryainov, Sergey; Udalov, Ihor (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Statement of the general problem. The oil and gas-bearing province of Eastern Ukraine is located in the Dnipro-Donetsk Basin (DDB). It covers the Paleozoic structural floor and is buried under younger sediments. The Paleozoic structural floor of the territory is represented as a long rift graben. The maximum thickness of the sedimentary cover in the graben is 15–17 km. According to geophysical data, the thickness of the earth’s crust is 31–32 km under the axial part of the DDB and increases towards the sides. But according to the maximum thickness and facies characteristics of the Paleozoic deposits, the thickness of the Earth’s crust below them could not exceed 20 km. The modern thickness is 1.5 times higher. Therefore, such a geological-geophysical model of the structure of the DDB is contradictory. Analysis of recent research and publications. The removal of the contradiction is possible due to the detection of a series of Hercynian thrusts with total amplitude of thrusts of the order of 50 km. Such thrusts began to be established on the northern and southern flanks of the DDB. Hercynian thrusts have a southwestern vergence. In the north, the Voronezh crystalline massif is pushed onto the DDB along the Noviy thrust with an amplitude of 9–10 km. In the south, the South Donbas melange zone is established, which pushes the folded Donbas onto the Ukrainian shield. On its continuation to the northwest is the southern side of the DDB - the so-called Southern monocline. The well-studied Pavlograd-Petropavlovsk coal mining district of Western Donbass with operating coal mines is located within its borders. An unsolved part of the overall problem. Numerous faults with relatively small amplitudes are established within the Paleozoic Southern Monocline. Together, they form a system of horsts and grabens with a north-western extension. But the bottom parts of the grabens are 1–3 km higher than the tops of the horsts. Such a geological situation is anomalous. This indicates the post-fault dislocation of the horst-graben system as a whole. The purpose of the article is identification of the causes of the anomalous structural position of the graben-horst system in the modern geological structure of the Southern Monocline and in the general model of the geological structure of Eastern Ukraine. Research materials and methods. Were involved more than 390 geological sections, constructed based on the data of more than 10,000 wells. Of them, 265 wells revealed the folds that are being analyzed. In addition, were used data of catagenetic transformations of the sedimentary section. Presentation of the main research material. The South Donbas mélange zone falls to the northeast and continues under the Southern Monocline. It is located in the upper block of this regional thrust structure and is in an allochthonous setting. According to geological data, the true amplitude of the thrust of Western Donbas on the Ukrainian shield is 15–20 km, and the vertical component of this amplitude exceeds 3 km. Such spatial parameters explain the abnormality of the structural position of the horsts and grabens of Western Donbass - their southwestern flanks were significantly raised relative to the northeastern flanks during thrusting. Scientific novelty. Therefore, in the modern geological structure, the Dnipro-Donetsk "basin" is not a rift, but a post-rift Hercynian folded region. It is formed by high-amplitude thrusts on the northern and southern flanks. The Hercynian fold region is buried under Mesozoic and Cenozoic sediments and is further complicated by Laramian and Attic fold-thrust dislocations of lesser intensity. Conclusions. The thrust model brings the geophysical parameters into the correspondence with the geological data and is confirmed by the actual material.